REFORMASI BIROKRASI DALAM PUSARAN POLITIK LOKAL: KAJIAN KEBIJAKAN PENINGKATAN AKUNTABILITAS DAN TRANSPARANSI DI KANTOR BUPATI KABUPATEN LABUHANBATU - Br Tambunan, Emi Ningsi; Muda, Indra (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This study investigates the intricate relationship between bureaucratic reform efforts, particularly in enhancing accountability and openness, and the dominant local political dynamics within the administrative offices of the Labuhanbatu Regency. Despite the presence of official commitments and policy frameworks supporting sound governance, their practical implementation at the regional level frequently encounters significant obstacles stemming from strong "local political currents." Utilizing a qualitative methodology and a case study design, this research analyzes how political interference, prevalent patronage practices, and electoral considerations substantially shape the formulation and execution of accountability and transparency policies. The findings indicate that accountability often manifests as a mere formality, access to information remains limited, and the oversight capacity of civil society and the media is suboptimal due to political pressure. Theoretically, this study enriches the understanding of the political-administrative interface and governance in context, asserting that bureaucratic transformation cannot be separated from the realities of power and political interests in the region. Practically, this research recommends more adaptive reform strategies, strengthening the independence of oversight, enhancing the integrity of public officials, and empowering civil society to achieve substantive accountability and transparency.